2016
DOI: 10.1007/s10549-016-4076-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of doctor–patient communication on patients’ perceptions of their risk of breast cancer recurrence

Abstract: Purpose Doctor-patient communication is the primary way women diagnosed with breast cancer learn about their risk of distant recurrence. Yet little is known about how doctors approach these discussions. Methods A weighted random sample of newly diagnosed early stage breast cancer patients identified through SEER registries of Los Angeles and Georgia (2013–2015) were sent surveys ~about 2 months after surgery (Phase 2, N=3930, RR 68%). We assessed patient perceptions of doctor communication of risk of recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 49 publications
1
30
0
1
Order By: Relevance
“…Discrepant understandings of prognosis or risk of future limitations between patients or their surrogates and their providers have been previously described in oncology and critical illnesses, with patients or surrogates typically being more optimistic than providers. 10,1820 These discrepant views have been attributed to misunderstandings, differences in beliefs, and lack of explicit discussions about risk, 18,19 and all of these elements are likely involved in parental misunderstanding of risk of impairment due to cancer and cancer treatment. While our study did not evaluate the reasons for limited parental understanding of risks of future limitations, previous work showed that late effects are discussed far less than acute effects of treatment in initial informed consent discussions.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepant understandings of prognosis or risk of future limitations between patients or their surrogates and their providers have been previously described in oncology and critical illnesses, with patients or surrogates typically being more optimistic than providers. 10,1820 These discrepant views have been attributed to misunderstandings, differences in beliefs, and lack of explicit discussions about risk, 18,19 and all of these elements are likely involved in parental misunderstanding of risk of impairment due to cancer and cancer treatment. While our study did not evaluate the reasons for limited parental understanding of risks of future limitations, previous work showed that late effects are discussed far less than acute effects of treatment in initial informed consent discussions.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in our prior work, cancer-related worry was associated with younger age and lower educational level, but not clinical factors. 10,11…”
Section: Discussionmentioning
confidence: 99%
“…Groups with higher rates of low health literacy included patients from remote areas, patients having lower income or low education, patients with age over 65, were generally in poor health conditions [15, 16]. Compared to those with adequate health literacy, individuals with limited health literacy had less knowledge about disease and treatment plans [17], less ability to correctly manage medication [1820], more problems in communicating with health care professionals [21, 22], poorer self-care skills [23, 24]. Patients with limited health literacy have high risk of delaying their decision to seek medical care, and experiencing negative health outcomes [2530].…”
Section: Introductionmentioning
confidence: 99%